Enlaces - Becker Ravest, Alex (AUS - Arquitectura / Urbanismo / Sustentabilidad, 2017)
http://www.auladelaigua.org/1enlaces.php http://www.h2opoint.com/ http://www.pre.nl/ http://www.aq.upm.eS/biblioteca/fondoantiguo/historiaconstruccion.html# Siglos%20XVI-XX http://www.paginadeinicio.cl/